Quantification of Growth of Campylobacter and Extended Spectrum β-Lactamase Producing Bacteria Sheds Light on Black Box of Enrichment Procedures - Hazeleger, Wilma C.; Jacobs-Reitsma, Wilma F.; den Besten, Heidy M. W. (Frontiers in Microbiology, 2016)
Campylobacter is well recognized as the leading cause of bacterial foodborne diarrheal disease worldwide, and is routinely found in meat originating from poultry, sheep, pigs, and cattle. Effective monitoring of Campylobacter contamination is dependent on the availability of reliable detection methods. The method of the International Organization for Standardization for the detection of Campylobacter spp. in food (ISO 10272-1:2006) recommends the use of Bolton broth as selective enrichment medium, including a pre-enrichment step of 4-6 h at 37°C to revive sublethally damaged cells prior to incubation for two days at 41.5°C. Recently the presence of abundantly growing extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL bacteria) has become one of the most important factors that interfere with the isolation of Campylobacter, resulting in false-negative detection. However, detailed growth dynamics of Campylobacter and its competitors remain unclear, where these would provide a solid base for further improvement of the enrichment procedure for Campylobacter. Other enrichment broths, such as Preston broth and Bolton broth plus clavulanic acid have been suggested to inhibit competitive flora. Therefore these different broths were used as enrichments to measure the growth kinetics of several strains of C. jejuni and ESBL bacteria separately, in co-culture and of strains in chicken samples. The maximum cell numbers and often the growth rates of Campylobacter in mixed culture with ESBL bacteria were significantly lower than in single cultures, indicating severe suppression of Campylobacter by ESBL bacteria, also in naturally contaminated samples. Preston broth and Bolton broth plus clavulanic acid successfully diminished ESBL bacteria and might therefore be a better choice as enrichment medium in possibly ESBL-bacteria contaminated samples. The efficacy of a pre-enrichment step in the Bolton broth ISO-procedure was not supported for cold-stressed and non-stressed cells. Therefore, omission of this step (4-6 h at 37°C) might be advised to obtain a less troublesome protocol.